Sustainability from the perspective of a Brazilian university: Discourse and relations with the Sustainable Development Goals - José Florentino Vieira de Melo; Ana Lúcia Araújo Lima Coelho (Revista Gestão Universitária na América Latina)
This article reports a study of the sustainability discourse manifested by a Brazilian Higher Education Institution, the Federal University of Paraiba. We based the research on comparing documents and institutional media and their influence on discursive formation. We employed Sociological Discourse Analysis as a research method to capture silences amid the speeches and to reveal ideologies that form actions and omissions. This way, we compared the discourse and the Sustainable Development Goals. Discursive positions, narrative configurations, and semantic spaces, considered with the Sustainable Development Goals as a parameter, revealed an organization that seeks to follow sustainability but with efforts on the social field, leaving other aspects linked to the theme in the background. The temporary closure of several organization sectors due to the COVID-19 pandemic muddled the observations and interviews. This fact may have limited our perception, impacting inferences and results. The research focused on the discourse of Higher-Level Institutions are not ordinary. Comparisons between organizational discourse and the Sustainable Development Goals can potentially reveal institutional commitments to the theme, as well as ideas that influence, positively or negatively, contexts and shared ideologies.